56 Can waiting times for urgent cabg be reduced to fall within national recommendations? insights from a large tertiary cardiac center. (6th June 2022) - Elamin, Ahmed; Muhammed, Eslam; Ahmad, Hasan; Bhatty, Asad; Appleby, Clare
Abstract : Introduction: Prolonged waiting times for urgent Coronary Artery Bypass Graft (CABG) are associated with adverse outcomes. Historically, analysis of inpatient CABG at Liverpool Heart and Chest Hospital (LHCH) between 11/2016–1/2017 identified a 10-day median time from referral to operation (interquartile range: 7–14). In an attempt to achieve the national 7 day target, the trust introduced changes to working patterns for surgical consultants including a surgeon of the week (SOW), and daily multidisciplinary team meetings (MDM). To evaluate the effect of these changes on achieving target, a further analysis was undertaken. Methods: LHCH is a stand alone cardiothoracic centre: referrals are direct from 7 partner hospitals (19%), or internally from cardiology team (81%). Retrospective data were collected for all patients who had non-elective CABG (excluding valve and aortic surgery) during two specified periods July-September 2019, April-July 2020. Data were extracted from electronic patient records, manually reviewed and cross checked to ensure accuracy. Results: Between July-September 2019, the median time from referral to operation for 109 eligible patients was 7 days (interquartile range: 6–9). 60% underwent CABG within 7 days for the group referred from LHCH directly, and only 25 % had their operation within 7 days for the group referred from other trusts. Between April-July 2020, 54 eligible patients were included. The median waiting time was 8 days (interquartile range: 6–10). 42% underwent CABG within 7 days for the group referred from LHCH directly. Similar trend observed in the group referred from other trusts with only 33% had their operation within 7 days. The distributions of waiting times were not significantly different between these two time periods (Mann-Whitney U test p-value 0.12), but there was a significant improvement compared to the 2016–17 cohort, where only 25 % referred from LHCH, and 18% referred from other trusts had their CABG within 7 days. Conclusions: Median waiting times for urgent CABG I significantly improved by implementing the SOW work pattern and daily MDMs.. Despite this, 40% percent still fail to have surgery within the recommended 7 days. This reflects a national picture, highlighted by the national audit of adult cardiac surgery (NACSA) and suggests that further improvements will require substantial resources. Conflict of Interest: None